2019
DOI: 10.1002/adma.201902493
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Method Correlating Raman Vibrational Characteristics to Chemical Expansion via Oxygen Nonstoichiometry of Perovskite Thin Films

Abstract: This article is protected by copyright. All rights reserved. track the frequency of the oxygen stretching mode around Fe 4+ , as it decreases during reduction as the material expands and increases during re-oxidation as the material shrinks. This methodology of oxygen pumping and in situ Raman of oxide films enables future in operando measurements even for small material volumes, as typical for applications of films as electrodes or electrolytes utilized in electrochemical energy conversion or memory devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 51 publications
1
41
0
Order By: Relevance
“…If this cell is employed as an oxygen pump against the material, a wide range of oxygen partial pressures can be covered by simply applying a voltage bias. [23,27,42] In this work, Ag/YSZ/LSF electrochemical cells were fabricated and afterwards measured in a special setup with electrical probes and a heating stage designed for in situ/operando spectroscopic ellipsometry analysis (Figure 3a inset and Experimental Section). As depicted in the inset of Figure 3a, DC voltage bias (ΔV) was applied between the LSF layer and the silver counter electrode both in anodic (ΔV > 0) and cathodic (ΔV < 0) modes.…”
Section: In Situ Ellipsometry Measurements As a Function Of Temperatumentioning
confidence: 99%
See 2 more Smart Citations
“…If this cell is employed as an oxygen pump against the material, a wide range of oxygen partial pressures can be covered by simply applying a voltage bias. [23,27,42] In this work, Ag/YSZ/LSF electrochemical cells were fabricated and afterwards measured in a special setup with electrical probes and a heating stage designed for in situ/operando spectroscopic ellipsometry analysis (Figure 3a inset and Experimental Section). As depicted in the inset of Figure 3a, DC voltage bias (ΔV) was applied between the LSF layer and the silver counter electrode both in anodic (ΔV > 0) and cathodic (ΔV < 0) modes.…”
Section: In Situ Ellipsometry Measurements As a Function Of Temperatumentioning
confidence: 99%
“…Finally, it was recently shown that Raman spectroscopy can also be used for tracking the oxygen non-stoichiometry of SrTi 1−x Fe x O 3−δ thin films. [27] Taking into consideration the benefits and limitations of the previous methods, an in situ ellipsometry technique is proposed here for quantifying the defect chemistry of LSF with x = 0.2, 0.4 and 0.5 (LSF20, LSF40 and LSF50, respectively) thin films through the measurements of optical conductivity. Ellipsometry is an optical spectroscopic technique based on the measure of the variation of polarization of a light beam reflected on a thin film sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To clarify the changes of switching symmetry in terms of the lithiation degree, we used in‐operando Raman spectroscopy to probe the A 1g vibration as a “marker” for titanium‐oxygen vibration upon applied external bias, Figure a. This methodology allows to probe the occupancy of the Wyckoff 8a and 16c structural positions that indicate local changes of the electronic states, and thus indicate metal–insulator transition.…”
mentioning
confidence: 99%
“…[ 44 ] With the introduction of “guest” and postmodification, the wrinkling peaks of the imidazole ring gradually shifted to lower wavenumber, which was caused by the lattice expansion process. [ 45 ] The results of time‐resolved photoluminescence (TRPL) (Figure 3c; see also Table S2, Supporting Information) confirmed that TCPP‐Fe was encapsulated in the open cavities of ZIF‐67, which result in a longer carrier lifetime (from 19.78 to 21.28 ns). The average emission lifetime of photoexcited charge for HZ@TCPP‐Fe was 21.83 ns, which was longer than that of HZ@TCPP‐Fe/Cu (12.03 ns), suggesting that excited‐state TCPP‐Fe connected with Cu 2+ .…”
Section: Resultsmentioning
confidence: 83%